Risk factors for post-extraction bleeding in patients with haemophilia: a retrospective cohort study. Issue 3 (April 2021) - Yagyuu, Takahiro; Yata, Sachiko; Imada, Mitsuhiko; Funayama, Naoki; Imai, Yuichiro; Yada, Koji; Nogami, Keiji; Kirita, Tadaaki
Abstract: Many guidelines and studies describe haemostatic management protocols for patients with haemophilia, but few have evaluated the risk factors for post-extraction bleeding. This retrospective cohort study was performed to investigate these risks among this group of patients. We used medical records to identify patients with haemophilia who underwent tooth extraction(s) between April 2006 and April 2019 in the Department of Oral and Maxillofacial Surgery at Nara Medical University Hospital, Nara, Japan, and conducted logistic regression analyses to identify risk or protective factors for post-extraction bleeding in procedures involving factor replacement therapy. Post-extraction bleeding was defined as bleeding that could not be stopped by biting down on gauze, and that required medical treatment between 30 min and 14 days after the extraction. A total of 151 extractions (84 interventions) in 55 patients fulfilled the inclusion criteria (130 extractions (72 interventions) in 48 patients with haemophilia A, and 21 extractions (12 interventions) in seven patients with haemophilia B). Post-extraction bleeding was observed in nine patients (16.3%), 10 interventions (11.9%), and 12 extractions (7.9%). On average, it occurred six days after the intervention, and on the fifth postoperative day after extractions. Use of mouth splints significantly reduced the risk (odds ratio: 0.13; p = 0.01) in patients on factor replacement therapy. We will conduct a prospective study to investigate the optimal type of splint and optimal splint-wearing period.